PERANCANGAN KAWASAN WISATA KULINER DENGAN PENDEKATAN PLACEMAKING - Alghifari, Muhammad Hanan; Hadinata, Irwan Yudha (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2025)
Banjarmasin as one of the largest cities in South Kalimantan has great potential in the tourism sector. One type of tourism that is developing quite rapidly is the culinary sector. This is indicated by the large number of workers absorbed in the culinary field. Realizing that Banjarmasin has great potential in the culinary tourism sector, the government has stepped in to develop the culinary tourism sector. However, the development carried out only sometimes runs smoothly, and in the process, several problems arise. Many visitors complain about the lack of supporting facilities, the place could be more visually attractive, the level of security could be better, and access is difficult. To solve this problem, culinary as a public place is used, formulated through the placemaking approach method. The concept of culinary as a public place emphasizes the relationship between user needs and the design object. Through the placemaking method approach, user comfort is implemented through arranging comfortable accessibility and circulation, providing supporting facilities, and adding the RTP function as a new attractive element to the object.